Cellular Delivery of Nanostructured Poly(amido amine) Dendrimers and Establishment of a Simple Methodology upon Ninhydrin Reaction: Cellular delivery of PAMAM and ninhydrin reaction - Alireza Nomani,; Ismaeil Haririan,; Rassoul Dinarvand,; Tarane Gazori,; Ebrahim Azizi,; Mohsen Aminic,; Jaleh Bararg,; Yadollah Omidig, (Iranian Journal of Pharmaceutical Sciences, 2010)
Dendrimer based nanostructures have been increasingly used for delivery of drugs/genes. These nanosystems, as non-viral gene delivery systems, were shown to have relatively high transfection efficiency despite exerting somewhat cytotoxicity. In this current investigation, poly(amido amine) (PAMAM) dendrimers, generation (G) zero to five, PEGylated PAMAM G3 and a new quaternized PAMAM G4 were synthesized and further characterized using FT-IR and 1H-NMR spectroscopies. The cellular uptakes and toxicity of these nanosystems were investigated using fluorescence microscopy and MTT assay, at which they revealed high internalization potential with low cytotoxicity in both T47D and MCF-7 cells. To establish a simple detection methodology, a ninhydrin reaction was performed on intact PAMAM full generations as well as PEGylated PAMAM G3 and quaternized PAMAM G4. Impacts of various factors such as reaction time, kinetic, reaction medium, and generation dependency of the reaction of dendrimers with ninhydrin were investigated. The best reaction conditions were determined and a simple and reproducible spectroscopic method was established. Upon these findings, we propose that this ninhydrin reaction based methodology may be considered as an easy approach for quantification of primary amines of nanostructured PAMAM dendrimer and its derivatives.